Gallbladder Stone Prevalence and Related Factors in Predialysis Chronic Kidney Disease Patients - Yılmaz, Üstün; İnci, Ayça; Özcan, Ercan; Gül, Semih; Berber, Hatice Gizem; Eşkin, Firdevs Pelin; Şahintürk, Yasin; Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2022)
Background: The aim of this study was to determine the prevalence and factors associated with gallbladder stone in patients with predialysis chronic kidney disease. Methods: This cross-sectional study retrospectively examined follow-up data of patients with chronic kidney disease between January 2015 and December 2020 at the Health Sciences University Antalya Training and Research Hospital who had undergone abdominal ultrasonography for any reason. Patients with gallbladder stone on abdominal ultrasonography and history of cholecystectomy due to gallbladder stone were identified as the gallstone group. The prevalence of gallbladder stone was determined according to disease stage. Patients with and without gallbladder stone were compared in terms of demographic and clinical characteristics and laboratory parameters that may be associated with the development of gallbladder stone. Results: A total of 511 patients had chronic kidney disease (stages 3, 4, and 5 in 303 [59.3%], 176 [34.4%], and 32 [6.3%], respectively). The gallstone prevalence rates were 25.1%, 30.1%, and 46.9% in stage 3, 4, and 5 chronic kidney disease, respectively, and that in all the patients was 28.2% (95% CI: 24.3-32.3, P = .026). Logistic regression analysis revealed that increased age (odds ratio: 1.045; 95% CI: 1.027-1.063, P < .001) and decreased estimated glomerular filtration rate (odds ratio: 0.974; 95% CI: 0.956-0.991, P = .004) were associated with gallbladder stone. Conclusion: The prevalence of gallbladder stone was high in the predialysis patients with chronic kidney disease and increased with increasing disease stage. High age and low estimated glomerular filtration rate were associated with gallbladder stone formation. Cite this article as: Yılmaz Ü, İnci A, Özcan E, et al. Gallbladder stone prevalence and related factors in predialysis chronic kidney disease patients. Turk J Gastroenterol. 2022;33(9):760-766.